The Effect of Puncture Load Cell Variation on Multi-Angle Layered Woven Fabric - A.A. Rahim, N.; F. Yahya, M.; A. Ghani, S. (International Journal of Engineering and Technology, 2019)
High tenacity polyester plain woven fabric punctured at multi angle layers were investigated. The main objective of the work was to analyse the effect of multi angle layered arrangement to quasi static puncture energy on different magnitude force. High tenacity polyester plain woven fabrics were weaved by using a rapier weaving machine at 300 rpm and 100% efficiency. The woven fabric samples consisted of different angles (90Âº, 0Âº, 45Âº and 135Âº). The maximum layers of woven fabric samples were two layers. The work was designed to evaluate the relationship between quasi static puncture energy of different load cell and multi angle layered of woven fabric. The results suggested that 10kN load cell gave the best value of puncture test and had been considered the appropriate force to test on woven fabrics.Â